Implementation of Student Learning (4C) During The Covid-19 Pandemic - Sri Lestari; Ambuy Sabur; Nurul Azizatul Latifah; Sutarman Sutarman (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
Learning implemantation by providing 4C skills (Critical Thinking, Communication, Collaborative, and Creativity) is one of the responsibilities of 21st century education, namely creating a quality workforce to be able to compete in the 21st century. This study aims to analyze and find out how much influence online learning and the role of parents in the learning implemantation. The population in this study was 656 students of class XI and XII of SMAN 14 Tangerang City for the Academic Year 2021/2022. Sampling was carried out using the Simple Random Sampling technique with a sample size of 268 students. Data collection techniques using questionnaires or questionnaires and data analysis using descriptive statistical analysis and multiple linear analysis with the help of IMB SPSS Version 25.0. The results of the research and discussion are 1) partially online learning has a positive and significant effect on the learning implemantation as indicated by the tcount 6.966 > ttable 1.969311 or p-value 0.000 <0.05. 2) partially the role of parents has a positive and significant effect on the learning implemantation as indicated by the tcount 2.726 > ttable 1.969311 or p-value 0.007 <0.05. 3) Simultaneously online learning and the role of parents on the learning implemantation have a positive and significant effect, as indicated by a p-value of 0.000 <0.05